Rapid Increase in Reports of Syphilis Associated With Men Who Have Sex With Women and Women Who Have Sex With Men, Japan, 2012 to 2016. Issue 3 (March 2018) - Takahashi, Takuri; Arima, Yuzo; Yamagishi, Takuya; Nishiki, Shingo; Kanai, Mizue; Ishikane, Masahiro; Matsui, Tamano; Sunagawa, Tomimasa; Ohnishi, Makoto; Oishi, Kazunori
Abstract : Background: In Japan, syphilis reports have recently increased rapidly. However, unlike other developed countries where men who have sex with men (MSM) were associated with the rise, the increase in Japan has been attributed more to men who have sex with women (MSW) and women who have sex with men (WSM). We report on this increase based on surveillance data. Methods: Syphilis is a notifiable disease requiring all laboratory-confirmed cases to be reported; stage and sex of the sex partner(s) suspected as the infection source are also reported. Focusing on primary and secondary (P&S) cases, we describe the temporal, demographic, and geographic distributions of reported cases in 2012 through 2016. Results: A total of 7040 (64.0%) of 10, 997 cases were P&S; the annual rate of increase was greatest for P&S and the proportion of P&S increased over time. Among P&S cases (1609 MSM, 2768 MSW, and 1323 WSM), MSW and WSM each surpassed MSM cases in 2016. Men were older with a wider age distribution (median, 37 years; interquartile range, 28–46 years) relative to women (median, 26 years; interquartile range, 21–34 years). Among women, 20- to 24-year-olds consistently had the highest reporting rate, reaching 9.0 per 100, 000 in 2016. Congenital syphilis reports increased from 0.4 in 2012 to 1.4 per 100, 000 live births in 2016. Although Tokyo prefecture had the highest reporting rate (3.98 per 100, 000 person-years), the proportionate contribution from Tokyo decreased in 2016. Conclusions: Reports on P&S syphilis increased yearly among MSW and WSM. Young women seem to be at particular risk, and with increased reports of congenital syphilis, syphilis prevention and control is currently a public health priority in Japan. Abstract : Recently, reports of syphilis have increased rapidly in Japan, with most cases being men who have sex with women and young women who have sex with men.